Anterior basolateral amygdala neurons comprise a remote fear memory engram - Hammack, Robert J.; Fischer, Victoria E.; Andrade, Mary Ann; Toney, Glenn M. (Frontiers in Neural Circuits, 2023)
Threatening environmental cues often generate enduring fear memories, but how these are formed and stored remains actively investigated. Recall of a recent fear memory is thought to reflect reactivation of neurons, in multiple brain regions, activated during memory formation, indicating that anatomically distributed and interconnected neuronal ensembles comprise fear memory engrams. The extent to which anatomically specific activation-reactivation engrams persist during long-term fear memory recall, however, remains largely unexplored. We hypothesized that principal neurons in the anterior basolateral amygdala (aBLA), which encode negative valence, acutely reactivate during remote fear memory recall to drive fear behavior. Using adult offspring of TRAP2 and Ai14 mice, persistent tdTomato expression was used to “TRAP” aBLA neurons that underwent Fos-activation during contextual fear conditioning (electric shocks) or context only conditioning (no shocks) (n=5/group). Three weeks later, mice were re-exposed to the same context cues for remote memory recall, then sacrificed for Fos immunohistochemistry. TRAPed (tdTomato+), Fos+, and reactivated (double-labelled) neuronal ensembles were larger in fear- than context-conditioned mice, with the middle sub-region and middle/caudal dorsomedial quadrants of aBLA displaying the greatest densities of all three ensemble populations. Whereas tdTomato+ ensembles were dominantly glutamatergic in context and fear groups, freezing behavior during remote memory recall was not correlated with ensemble sizes in either group. We conclude that although an aBLA-inclusive fear memory engram forms and persists at a remote time point, plasticity impacting electrophysiological responses of engram neurons, not their population size, encodes fear memory and drives behavioral manifestations of long-term fear memory recall.